Natural Compounds Such as Hericium erinaceus and Coriolus versicolor Modulate Neuroinflammation, Oxidative Stress and Lipoxin A4 Expression in Rotenone-Induced Parkinson’s Disease in Mice - Cordaro, Marika; Modafferi, Sergio; D’Amico, Ramona; Fusco, Roberta; Genovese, Tiziana; Peritore, Alessio Filippo; Gugliandolo, Enrico; Crupi, Rosalia; Interdonato, Livia; Di Paola, Davide; Impellizzeri, Daniela; Cuzzocrea, Salvatore; et al. (Biomedicines, 2022)
Background: A growing body of research suggests that oxidative stress and neuroinflammation are early pathogenic features of neurodegenerative disorders. In recent years, the vitagene system has emerged as a potential target, as it has been shown to have a high neuroprotective power. Therefore, the discovery of molecules capable of activating this system may represent a new therapeutic target to limit the deleterious consequences induced by oxidative stress and neuroinflammation, such as neurodegeneration. Lipoxins are derived from arachidonic acid, and their role in the resolution of systemic inflammation is well established; however, they have become increasingly involved in the regulation of neuroinflammatory and neurodegenerative processes. Our study aimed at activating the NF-E2-related factor 2 (Nrf2)/heme oxygenase 1 (HO-1) redox system and increasing lipoxin A4 for the modulation of antioxidant stress and neuroinflammation through the action of two fungi in a rotenone-induced Parkinson’s model. Methods: During the experiment, mice received Hericium erinaceus, Coriolus versicolor or a combination of the two (200 mg/kg, orally) concomitantly with rotenone (5 mg/kg, orally) for 28 days. Results: The results obtained highlighted the ability of these two fungi and, in particular, their ability through their association to act on neuroinflammation through the nuclear factor-kB pathway and on oxidative stress through the Nrf2 pathway. This prevented dopaminergic neurons from undergoing apoptosis and prevented the alteration of typical Parkinson’s disease (PD) markers and α-synuclein accumulation. The action of Hericium erinaceus and Coriolus versicolor was also able to limit the motor and non-motor alterations characteristic of PD. Conclusions: Since these two mushrooms are subject to fewer regulations than traditional drugs, they could represent a promising nutraceutical choice for preventing PD.